(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In this paper, we describe the language used in a particular educational video game, Quest Atlantis (QA). We begin by reviewing a number of works which deal with video games and come to the conclusion that, although many speak of aligning the player with a particular identity (cf. footing, Goffman, 1981) which is necessary to achieve particular tasks, none of these works deal specifically with the role language plays in the construction of these personae. Therefore, we describe the language used in a single task in QA, revealing the generic structure (Hasan, 1985) of these prompts. After that, we observe how language is used at the level of the sentence with the analysis of deictics (Ochs, 1992; Hanks, 1992). We conclude that more interactions within QA need to analyzed before we reach a more definite answer to our questions, but the language resources revealed here will certainly provide educators and game with a more tangible framework with which to position learners and players.